Climate shocks, household food security and welfare in Afghanistan - Hayatullah Ahmadzai; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2024)
The increasing impact of natural disasters (floods, earthquakes, landslides, and avalanches) in Afghanistan, notably flooding and similar climate shocks, poses a growing concern as vulnerability to climate change intensifies the potential severity of these impacts in future. This paper uses two household surveys (2011/12 and 2013/14) combined with other data to assess the effects of climate shocks (especially floods) on the welfare of agricultural households, allowing also for conflict and price shocks. We evaluate the impacts of shocks on several measures of food security, dietary diversity, household food consumption spending, farm revenue and income comparing affected to non-affected households. The analysis is based on endogenous switching regressions (ESR) and propensity score matching (PSM) allowing for selection bias and addressing endogeneity. Floods are the main shock and have significant adverse effects on food security and welfare indicators. For example, the estimated average treatment effect in 2013-14 implies a decrease of about a third in food consumption expenditures, with similar reductions in household income and farm revenue. The findings highlight the need for better disaster risk reduction and planing strategies to support affected populations to respond to and recover from climate shocks.
Keywords: Q12; Q54; O12; O13; D12; 330; Natural disasters; household food security; household welfare; econometric methods; disaster risk management; conflict; Afghanistan